2020
DOI: 10.21577/0103-5053.20190197
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Phenolic Acids by Triple Quadrupole Mass Spectrometry with Electrospray Ionization in Negative Mode and H/D Isotopic Exchange

Abstract: This work reports the theoretical and experimental study of fragmentation reactions in the gas phase of five phenolic acids using triple quadrupole mass spectrometry by electrospray ionization in negative ionic mode, as well as the isotope exchange experiments. MS/MS spectra were analyzed to suggest the fragmentation mechanisms, while theoretical calculations at the theory level B3LYP/6-311+G** were performed to expose the proposed mechanisms viability for this class of compounds. As expected, compounds with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
3
9
1
Order By: Relevance
“…Compounds 1, 2 and 3 were identified as p-, m-and o-coumaric acid, respectively, with the same deprotonated molecular ion [M-H] − of m/z 163.0401 and the major fragment ion at m/z 119.0501 (Table 1). The main fragment ion of caffeic acid 6 was m/z 135.0451 (neutral loss of CO 2 , 44 amu, from [M-H] − ) Sinosaki et al, 2020). One study identified the presence of ferulic acid 5 in PC microgreens, although this was not seen in the current study which could imply that under the current combined lighting and photon flux the accumulation of 5 was inhibited (Kyriacou et al, 2020).…”
Section: Hydroxycinnamic/benzoic Acids and Derivativescontrasting
confidence: 59%
“…Compounds 1, 2 and 3 were identified as p-, m-and o-coumaric acid, respectively, with the same deprotonated molecular ion [M-H] − of m/z 163.0401 and the major fragment ion at m/z 119.0501 (Table 1). The main fragment ion of caffeic acid 6 was m/z 135.0451 (neutral loss of CO 2 , 44 amu, from [M-H] − ) Sinosaki et al, 2020). One study identified the presence of ferulic acid 5 in PC microgreens, although this was not seen in the current study which could imply that under the current combined lighting and photon flux the accumulation of 5 was inhibited (Kyriacou et al, 2020).…”
Section: Hydroxycinnamic/benzoic Acids and Derivativescontrasting
confidence: 59%
“…Compound 14 showed a [M-H] − ion at m / z 179 and was identified as caffeic acid. According to the literature data, the base peak ion at m / z 135 [M-H-CO 2 ] − and the fragment ions at m / z 161 [M-H-H 2 O] − and m / z 151 [M-H-CO] − highlighted the presence of a carboxylic acid and a phenolic group [ 35 ]. Two feruloylquinic acid isomers (compounds 15 and 27) were putatively identified.…”
Section: Resultsmentioning
confidence: 99%
“…The fragment ions at m / z 145 [M-H-H 2 O] − , m / z 135 [M-H-CO] − and m / z 93 [M-H-CO 2 -C 2 H 2 ] − suggested the presence of a phenolic group and the hydroxycinnamic acid moiety. According to the mass fragmentation pattern, compound 29 was annotated as p-coumaric acid [ 35 ]. Compound 34 displayed a [M-H] − ion at m / z 193 and a base peak ion at m / z 149 [M-H-CO 2 ] − .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group 1 includes conjugates of gallic acid with sugars and small organic acids ( Figure 4 ). Fragmentation patterns of these compounds are characterized by the ions of m / z 169 (gallate) and 125 (3,4,5-trihydroxybenzene, ion derived from the decarboxylation of the gallate) [ 50 , 51 ]. If a sugar unit is present, common losses of H 2 O and consecutive losses of C 2 H 4 O 2 units from the residual hexose and the heterolytic cleavage of the sugar are observed [ 52 ].…”
Section: Resultsmentioning
confidence: 99%